2017
DOI: 10.1186/s13023-017-0600-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and population pharmacokinetics of sapropterin in PKU patients <4 years: results from the SPARK open-label, multicentre, randomized phase IIIb trial

Abstract: BackgroundSapropterin dihydrochloride, a synthetic formulation of BH4, the cofactor for phenylalanine hydroxylase (PAH, EC 1.14.16.1), was initially approved in Europe only for patients ≥4 years with BH4-responsive phenylketonuria. The aim of the SPARK (Safety Paediatric efficAcy phaRmacokinetic with Kuvan®) trial was to assess the efficacy (improvement in daily phenylalanine tolerance, neuromotor development and growth parameters), safety and pharmacokinetics of sapropterin dihydrochloride in children <4 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…The effectiveness of BH 4 treatment has been demonstrated in a number of short-term [ 16 19 ] and long-term studies [ 18 , 20 24 ], which have included patients aged 0–4 years and shown the benefit of treatment in this age range. The advantages of initiating BH 4 therapy at an early age include increasing natural protein intake during a critical time of growth and development and increasing the likelihood of adherence to treatment [ 22 ]. Accordingly, in 2015, approval of sapropterin was extended in Europe to children aged 0–4 years [ 15 , 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effectiveness of BH 4 treatment has been demonstrated in a number of short-term [ 16 19 ] and long-term studies [ 18 , 20 24 ], which have included patients aged 0–4 years and shown the benefit of treatment in this age range. The advantages of initiating BH 4 therapy at an early age include increasing natural protein intake during a critical time of growth and development and increasing the likelihood of adherence to treatment [ 22 ]. Accordingly, in 2015, approval of sapropterin was extended in Europe to children aged 0–4 years [ 15 , 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of initiating BH 4 therapy at an early age include increasing natural protein intake during a critical time of growth and development and increasing the likelihood of adherence to treatment [ 22 ]. Accordingly, in 2015, approval of sapropterin was extended in Europe to children aged 0–4 years [ 15 , 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations